Clinical and psychosocial outcomes of obstetrics Fistulae in Sub-Saharan Africa: a review of Literature. (2020)
Obstetrics fistulae are preventable and treatable diseases of immense public health importance which render women debilitated and devastated with physical, mental, psychological, economic and social problems. It is prevalent among the less privileged with limited access and utilization of reproductive health services which reflect the state of health care delivery especially emergency obstetric care in a country. Over the years, the impact of obstetrics fistulae has led to several studies on the prevalence, clinical outcome and experiences of affected women, but there is paucity of information on the psychosocial and economic impact of obstetrics fistulae in developing countries. This review is therefore an attempt to bridge this gap and hopefully point attention to the need to consider these impacts when designing further interventions for patients with Obstetrics fistulae.